Management of Agitation Following Aneurysmal Subarachnoid Hemorrhage: Is There a Role for Beta-Blockers? - Fayaz Ibrahim; Ramaswamy Viswanathan (Case Reports in Psychiatry)
Introduction. Stroke is a leading cause of mortality and morbidity in the United States. About 20% of the stroke is hemorrhagic and about 50% of these is due to aneurysmal subarachnoid hemorrhage. A troublesome neuropsychiatric complication of subarachnoid hemorrhage is agitation/aggression. Case Presentation. A 45-year-old man with no prior psychiatric history, sustained subarachnoid hemorrhage. After initial stabilization for 2 days, he underwent craniotomy and clipping of anterior cerebral communicating artery aneurysm. Treatment was continued with labetalol, nimodipine, and levetiracetam. Beginning postoperative day 4, patient developed episodes of confusion and agitation/aggression. Switching of Levetiracetam to valproate did not show any improvement. Psychiatry team tried to manage him with intense nursing intervention and different medications like olanzapine, valproate, lorazepam, and haloperidol. However, patient continued to be agitated and aggressive. Switching from labetalol to metoprolol resulted in dramatic improvement within 3 days. Discussion. Antipsychotics and benzodiazepines are often not sufficiently effective in the control of agitation/aggression in patients with traumatic brain injury and similar conditions. Our case report and the literature review including a cochrane review suggests that beta-blockers may be helpful in this situation.